Influence of processing aids and hydroxyapatite as fillers on flow behaviour and mechanical properties of ultra high molecular weight polyethylene/high density polyethylene composites - Ahmad, Mazatusziha (Trans Tech Publications, 2011)
In this study, blends of ultra high molecular weight polyethylene/high density polyethylene/polyethylene glycol (UHMWPE/HDPE/PEG) and the composites containing Hydroxyapatite (HA) as reinforcement filler were prepared via single screw extruder nanomixer followed by compression moulding. PEG (2phr) was used as processing aid and HA loadings were varied from 10 to 50 phr. HDPE and PEG were introduced to improve the extrudability of UHMWPE. Rheological behavior was studied via capillary rheometer while flexural and izod impact tests were conducted in order to investigate the mechanical properties of the blends and composites. Melt viscosity of the blends was found to decrease with increasing shear rate indicating a pseudoplastic behaviour. Incorporation of PEG shows a synergism effect on the reduction of blends viscosity. Blend of 40% UHMWPE/ 60% HDPE/ 2 phr PEG was chosen as the optimum blend composition with a balance properties in terms of the mechanical properties and processability. The incorporation of HA fillers from 10 to 50 phr into the blend resulted in the increase of flexural modulus and flexural strength with a slight decline of impact strength values. It can be concluded that the composites having adequate strength and modulus within the range of cancellous bone properties were succesfully developed to be used as biomedical implant devices.